2011
DOI: 10.4300/jgme-d-10-00070.1
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Intensive Care Simulation Course: A New Paradigm in Teaching

Abstract: Objective True pediatric emergencies are rare. Because resident work hours are restricted and national attention turns toward patient safety, teaching methods to improve physician performance and patient care are vital. We hypothesize that a critical-care simulation course will improve resident confidence and performance in critical-care situations. Interventions We developed a monthly pediatric intensive care unit simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
1
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 21 publications
0
29
1
7
Order By: Relevance
“…4 We showed that procedure simulation workshops significantly improve resident self-reported procedural confidence and competence for all procedures assessed and all levels of training. Among other studies that evaluated resident procedure workshops, Tofil et al 10 reported that a pediatric intensive care unit simulation course that used high-fidelity pediatric simulators improved pediatrics residents9 confidence in intubation and intraosseous line placement. In that study, however, video review of performance by pediatric critical care physicians using checklists showed a discordance between objective performance and self-assessment.…”
Section: Discussionmentioning
confidence: 99%
“…4 We showed that procedure simulation workshops significantly improve resident self-reported procedural confidence and competence for all procedures assessed and all levels of training. Among other studies that evaluated resident procedure workshops, Tofil et al 10 reported that a pediatric intensive care unit simulation course that used high-fidelity pediatric simulators improved pediatrics residents9 confidence in intubation and intraosseous line placement. In that study, however, video review of performance by pediatric critical care physicians using checklists showed a discordance between objective performance and self-assessment.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Although this is not definitive, we have anecdotal evidence that after the simulation training, 3 residents performed chest tube insertions in the NICU successfully, and reported that the simulation training had helped them tremendously.…”
Section: Discussionmentioning
confidence: 98%
“…HPS sessions can be video recorded, providing a valuable source of feedback and meaningful evaluation based on measurable criteria. 8,[11][12][13][14] We hypothesized that HPS would enhance a residentas-teacher training program in our institution by allowing fellows to gain experience teaching residents and medical students while enabling close observation of the fellows leading sessions.…”
Section: Introductionmentioning
confidence: 99%